Analisis Implementasi Keselamatan dan Kesehatan Kerja (K3) Pada Pekerja Proyek Pembangunan Gedung Baru RSU Lawang Medika, Kecamatan Lawang, Kabupaten Malang - Antonius Dandi; Fifi Damayanti; Andy Kristafi Arifianto (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Construction is a high-risk sector that demands serious attention to Occupational Safety and Health (OSH), given its significant contribution to workplace accident statistics. This study aims to analyze OSH implementation at the new RSU Lawang Medika hospital construction project in Malang. Using a quantitative method involving observation, documentation, and interviews, the results show varying levels of PPE compliance. The highest compliance was observed for safety shoes and vests, followed by adequate use of gloves, while the use of helmets and masks remained very low. Overall, the level of PPE implementation falls into the moderate category and shows an increase on higher floors. This study concludes that strict supervision, structured OSH programs, and high-quality PPE play a vital role in creating a safe work environment on construction projects.